The evolution of the consumption behavior of rural households in China: logical motivation and policy responses - Tian, Zhen; Bian, Xing Yu; Tan, Yan (Frontiers in Sustainable Food Systems, 2025)
Based on provincial panel data from rural household surveys in China from 1978 to 2021, this paper constructs an econometric model of rural household consumption behavior covering the influencing factors of income level, habit formation, uncertainty and the urbanization degree etc. The SYS-GMM estimation method is applied to empirically study the basic logic and general rules of the evolution of rural household consumption behavior in three different stages of China’s well-off society construction practices since the reform and opening-up. The results indicate that the motivators of evolution of rural household consumption in China have shifted from purely endogenous and demand-side factors to the combined effects of endogenous and exogenous factors as well as supply-side and demand-side factors since the reform and opening up. Therefore, in the context of global economic slowdown with challenges to economic globalization, it becomes crucial to adopt the strategy that can effectively synchronize supply-side structural reforms with demand-side structural adjustments based on the practical situations of China’s rural households. Such a strategy is geared towards fostering a more advanced dynamic equilibrium that is propelled by demand-induced supply and supply-generated demand, aiming to enhance rural consumption, stimulate the domestic economic cycle and fulfill the people’s growing aspirations for a more prosperous life.